IPTEKS E-FILING TERHADAP WAJIB PAJAK PADA KPP PRATAMA MANADO - Rorimpandey, Mutiara Deivana; Lambey, Robert (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
KPP Pratama Manado is a place provided by the government for the public or taxpayer in carrying out their obligations to report on each asset or wealth or income they have. Along with the times in the advancement of information and communication technology, KPP Pratama Manado provides convenience for taxpayer in reporting SPT (Surat Pemberitahuan Tahunan) by providing e-Filing. The e-Filing system is an online tax reporting system that has been provided by the government for taxpayer. However, the lack of knowledge of taxpayer on e-Filing system affects taxpayer still reporting annual SPTs manually. KPP Pratama Manado should further improve the grade and quality of e-Filing system so that they can be used more optimally by taxpayer.Keywords: SPT, e-Filing, taxpayer